Risk profiles for cybercrime victimization: a conjunctive analysis of case configurations - van ‘t Hoff-de Goede, Maria Susanne (Deviant behavior, 2025)
It is crucial to understand who is at risk for cybercrime victimization. This study draws on longitudinal data from the Online Behavior and Victimization Study (N = 1886) to establish high-risk victimization profiles for cybercrime in general, hacking, malware infection, and fraud. We use Conjunctive Analysis of Case Configurations (CACC) to identify 64 dominant profiles describing personal characteristics (e.g., age, self-control), routine activities (e.g., exposure) and actual self-protective online behavior (e.g., password management) in 1330 respondents. After noting that observations moderately and statistically significantly cluster around dominant profiles, we identify ten high-risk profiles associated with an 18-50% probability of cybercrime victimization within the next year. Examining contextual variability in profiles reveals that self-control is most associated with malware infection, and fraud victimization.